1997
DOI: 10.1046/j.1365-3059.1997.d01-199.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of root‐knot disease of tomato by the application of fly ash in soil

Abstract: The effects of fly ash at different concentrations (0, 10, 20, 30 .. .100% vol./vol. in soil) on plant growth and yield were investigated in tomato plants infected or noninfected with root-knot nematode, Meloidogyne incognita (2000 juveniles per plant) in clay pots. An increase in fly ash concentration in the soil correspondingly increased the availability of carbonates, bicarbonates, sulphate, chlorides, B, P, K, Ca, Mg, Mn, Cu and Zn in the soil. The porosity, water-holding capacity, pH, conductivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 12 publications
(18 reference statements)
1
12
0
1
Order By: Relevance
“…The substantial effect probably lies thereby in a reduction of the photosynthetic product. This assumption is confirmed by findings that fly-ash dust from a coal-fired power plant affected Calamagrostis epigeios and Hypericum perforatum but the stomata were rarely blocked [34] . They suggested that the dust may act directly on the guard cells, though the mechanisms for this effect remain uncertain till date.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The substantial effect probably lies thereby in a reduction of the photosynthetic product. This assumption is confirmed by findings that fly-ash dust from a coal-fired power plant affected Calamagrostis epigeios and Hypericum perforatum but the stomata were rarely blocked [34] . They suggested that the dust may act directly on the guard cells, though the mechanisms for this effect remain uncertain till date.…”
Section: Discussionsupporting
confidence: 52%
“…A further explanation lies probably in the very high CFA proportions in the substrate (90-95%) used by other groups [23] . The effect of different portions of fly ash in the substrate has been tested by on the crop yield of tomatoes [34] . Here an increase of the CFA concentration in the soil increased the availability of carbonates, sulphates, chloride, B, P, K, Ca, Mg, Mn, Cu and Zn.…”
Section: Discussionmentioning
confidence: 99%
“…Nematode might have lost its activities and later could not survive under the stress of fly ash. Losing the activity and not reaching the mature stage of M. incognita is very important for the agriculture point of view, because there will be no loss to the crop (Khan 2007, Iram 2010. Thus soil application of fly ash with 30% level is useful, as it suppresses the, M. incognita one hand, and improves the Pumpkin crop on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Fly ash has been suggested as a potting mixture (Menzies and Aitken 1996) and has potential to reduce root disease (Khan et al 1997(Khan et al , 2011Pandey et al 2009). Fly ash, a by-product of coal combustion, is generated in coal-based thermal power plants ) and its disposal as a waste material is a serious problem worldwide.…”
Section: Methodsmentioning
confidence: 99%